EVALUASI PELAKSANAAN MANAJEMEN PROGRAM ( PIK - KRR ) PUSAT INFORMASI DAN KONSELING KESEHATAN REPRODUKSI REMAJA OLEH PENYULUH KELUARGA BERENCANA DI KABUPATEN JEMBER TAHUN 2011 - K Kiswati (Jurnal Ilmu Kesehatan Masyarakat, 2012)
KRR problem in Jember (HIV/AIDS, drug, sexuality) and high early marriage. PIK-KRR program implementation by the extension of family planning has not reached all the targets, suspected cause is a commitment that is less optimal than the coach and cross-linked sectors that affect the provision of essential resources in the implementation of policy programs such as funding, infrastructure/facilities and equipment. This type of qualitative research is descriptive, cross sectional approach. Data collection is done by in-depth interview technique (indepth interviews) Analysis of data using the content description of processing methods (content analysis). The results of the implementation of the PIK-KRR is already support from the Regents muddy in the form of SK, but not yet supported by the funds, facilities/amenities are pretty as the motor of the implementation of programs, media campaigns and socialization in quality and quantity is inadequate, the empowerment of human resources by PKB has not been that affect the optimal promotional activities and socialization, yet comprehensive partnership both cross and cross-sectoral programs supported the MoU. Administration system in accordance with the guidelines, but the reporting system has not been routinely every month. Quantity and quality of coaching is less. The conclusion that the implementation of the PIK-KRR Program has not been done properly in accordance with guidelines. Based on this study then recommended continued policy of PIK-KRR and BPPKB need to advocate on policy makers, across sectors/programs on the strategic value of youth service.   Keywords : PIK-KRR, Implementation, PKB